PENGARUH KOMPETENSI MANAJERIAL KEPALA SEKOLAH DAN TUNJANGAN SERTIFIKASI GURU TERHADAP KINERJA GURU SMP KOTA PRABUMULIH - Yeni Indriati; Yasir Araffat; Nurlina Nurlina (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to find out and describe the effect of the principal's managerial competence and teacher certification allowance on the performance of teachers at SMP Kota Prabumulih. This research is a survey research with a quantitative approach. The subjects of the study were principals and teachers at SMP Negeri Prabumulih who were the object of research. The results showed that there was an influence of the principal's managerial competence and teacher certification allowance on teacher performance. this can be seen in the count (5.525) > ftabel (3.12) with ho rejected and ha accepted indicated by the regression line equation Y = 1.678 + 0.797x1 + 0.701x2 meaning, there is an influence of the principal's managerial competence and teacher certification allowance on teacher performance. The principal's managerial competence and teacher certification allowance were able to affect teacher performance with a contribution of 87.4% while the remaining 12.6% was influenced by other variables that were not studied in this study. In conclusion, the principal's managerial competence and teacher certification allowance influence the performance of Prabumulih City Middle School teachers. Keywords: Certification Allowance, Managerial Competence, Teacher Performance